2020
DOI: 10.1016/j.athoracsur.2019.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Can Preoperative C-Reactive Protein Predict Bleeding After On-Pump Coronary Artery Bypass Grafting?

Abstract: Background. Bleeding after cardiac surgery remains a challenge. Numerous studies suggest that higher level of C-reactive protein (CRP) increases cardiovascular risk. There is limited information revealing the association of preoperative CRP concentration and postoperative bleeding while undergoing on-pump coronary artery bypass grafting (CABG). This study aimed to investigate the relationship between preoperative CRP level and postoperative bleeding within 24 hours after CABG.Methods. Data on 1055 patients acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Fibrinogen has become known as a systemic biomarker of inflammation, similar to CRP, tumour necrosis factor-α, and interleukin ( 17 ). Levels of fibrinogen were correlated with CRP after adjustment for potential confounders, which has also been demonstrated in our previous studies ( 8 ). Furthermore, elevated circulating fibrinogen levels are associated with an increased risk of cardiovascular disease, such as coronary heart disease and stroke ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Fibrinogen has become known as a systemic biomarker of inflammation, similar to CRP, tumour necrosis factor-α, and interleukin ( 17 ). Levels of fibrinogen were correlated with CRP after adjustment for potential confounders, which has also been demonstrated in our previous studies ( 8 ). Furthermore, elevated circulating fibrinogen levels are associated with an increased risk of cardiovascular disease, such as coronary heart disease and stroke ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 86%
“…A chronic low-grade inflammatory state is associated with increased plasma levels of inflammatory markers ( 7 ). Another previous study found that preoperative C-reactive protein (CRP), as a marker of inflammation, was also associated with body mass index (BMI), activated partial thromboplastin time, and fibrinogen levels ( 8 ). Other studies have shown that patients with COVID-19 admitted with hyperinsulinemia, hyperglycemia, and hypertension had increased inflammation, coagulation, and thrombosis risk ( 9 ), and that hyperglycemia potentiated the prothrombotic effect of aldosterone in a rat model of arterial thrombosis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have attempted to predict thromboembolism or neurobehavioral outcomes using preoperative blood biochemical indicators (5,6), studies on the association between preoperative blood biochemical indicators and other postoperative complications and mortality are insufficient. A large number of studies have shown that the preoperative inflammatory state of patients undergoing cardiovascular surgery is closely related to the incidence and all-cause mortality of postoperative complications, including bleeding, deep wound infection, and mortality (7)(8)(9)(10)(11)(12). Currently, the main method to assess an inflammatory state is the testing of blood biomarkers, which is easy to access and apply.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that CRP might be involved in the coagulation process during CABG. Previous study found that CRP was another indicator of bleeding after on-pump CABG [12]. Cardiopulmonary bypass (CPB) may induce an inflammatory response, which may be involved in the coagulation process.…”
Section: Introductionmentioning
confidence: 99%